MRI Study in Patients with Idiopathic Cokearthrosis of the Hip Joint - Saodat, Asilova; Vohid, Akramov; Ravshan, Nazarov; Shamshod, Ahmedov (International Journal of Psychosocial Rehabilitation, 2020)
MRI is the optimal method for diagnosing hip lesions in patients with idiopathic coxaarthrosis. Magnetic resonance imaging (MRI) is a safe and painless research method with which you can get a detailed image of various organs and other body structures. The advantage of this method is the ability to study various soft tissues and organs, much more accurately than when using other methods. In some cases, the method makes it possible to assess the function of organs, allows us to ascertain the presence of damage in the early stages of the disease.